Klasifikasi Tongue Tie Berdasarkan Kadar Billirubin Bayi Baru Lahir - Kartikawati, Febriana; Bachri, Syaiful; Karnasih, I Gusti Ayu (Malang Journal of Midwifery (MAJORY), 2021)
Tounge tie is a variation of the anatomy of the tongue frenulum, the frenulum being shorter and thicker than normal shape. This incident is experienced in many infants (General & General, 2013). Based on a preliminary study conducted at the Jember Clinic Hospital in August 2019, it was found that 20% of 45 baby births had tongue tie. This study aims to determine the relationship between tongue tie classification and billirubin levels of newborns at the Jember Regency Private Hospital. This type of research is a quantitative study with cross sectional approach. The population of 22 infants aged 0-7 days in January 2020 to April 2020 and obtained a sample of 22 babies using the incidental sampling technique. Data collection instruments using the patient's medical record file. Measuring instruments used are intervals and nominal with Spearman rho analysis using 2 tails significance with a confidence level of 95% (? = 0.050). The results showed a significant value <0.050 (0,000 <0.050) which means that there was a significant relationship between the tongue tie classification variable and the variable billirubin content. For health workers, especially midwives need to improve the ability to identify babies with tongue tie to prevent the increase in billirubin levels in newborns. Keywords: Tongue tie, Tie Classification And Billirubin Levels